More than a snapshot: dynamic value-in-use emergence in e-services - Nicole Bulawa; Frank Jacob (Electronic Markets, 2021)
Supporting consumers' value-in-use (ViU) emergence throughout a usage process has become increasingly challenging as, in today's environment, usage has shifted from discrete events to continuous e-service interactions. Although researchers acknowledge that ViU is dynamic and evolves over time, most studies treat it as a static concept. Using the empirical context of language learning applications, the authors adopt a dynamic perspective on e-service ViU and extend it with regulatory mode theory using a qualitative approach. By applying the underlying functions of self-regulation: locomotion and assessment, the authors investigate how ViU emerges throughout a usage process and establish an eight-stage ViU emergence process, ranging from initial trigger to termination. By examining a consumer's usage, assessments, and movements, practitioners can pinpoint a consumer's location in the ViU emergence process and take appropriate measures to further promote ViU emergence in e-services.
Keywords: M31; 620; Value-in-use; Value-in-use emergence; e-services; Regulatory mode theory; Mobile application usage